2015
DOI: 10.1161/circheartfailure.114.001658
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Trial of Gene Expression Profiling Versus Heart Biopsy in the First Year After Heart Transplant

Abstract: Background-The endomyocardial biopsy (EMB) is considered the gold standard in rejection surveillance post cardiac transplant, but is invasive, with risk of complications. A previous trial suggested that the gene expression profiling (GEP) blood test was noninferior to EMB between 6 and 60 months post transplant. As most rejections occur in the first 6 months, we conducted a single-center randomized trial of GEP versus EMB starting at 55 days post transplant (when GEP is valid). Methods and Results-Sixty heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 16 publications
2
59
0
Order By: Relevance
“…The IMAGE 3 and E-IMAGE 24 studies have demonstrated that the number of surveillance biopsies was safely reduced while the clinical outcomes of patients managed with GEP surveillance were non-inferior to outcomes in patients managed with the biopsy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The IMAGE 3 and E-IMAGE 24 studies have demonstrated that the number of surveillance biopsies was safely reduced while the clinical outcomes of patients managed with GEP surveillance were non-inferior to outcomes in patients managed with the biopsy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest these “high‐risk” patients should include, but not be limited to, sex‐mismatched recipients and those with first‐year ACR, as indicated by our findings. Patients who do not qualify as “high risk” could instead be considered for novel noninvasive genomic surveillance for ACR such as gene expression profiling (GEP; AlloMap ® : CareDx, Brisbane, CA, USA), which has shown able to reliably rule out severe ACR in asymptomatic “low‐risk” patients later than 6 months post‐HT, and possibly even earlier than that …”
Section: Discussionmentioning
confidence: 99%
“…While the IMAGE study design decision allowed/necessitated the redefinition of rejection, it also motivated the Early‐IMAGE (E‐IMAGE) study that confirmed the early CARGO study results of AlloMap use in the period between day 56 and 180 post‐heart transplantation …”
Section: Allomap Phase 3: Clinical Strategy Comparison—image Studymentioning
confidence: 96%
“…E-IMAGE also confirmed early observations by the CARGO investigators of the safety of immunosuppression (prednisone) weaning using AlloMap as guidance in the period between day 56 and 180 postheart transplantation. 28…”
Section: Practice Paradigm Implication #5mentioning
confidence: 99%